The effect of chemical agents on the productivity of crop rotations with legumes and cereals in the conditions of unstable moisture in the south of the Non-Black Soil Zone of Russia - L. N. Prokina; S. V. Pugaev (Аграрная наука Евро-Северо-Востока, 2021)
The article summarizes the results of 1990-2012 research conducted during the stationary experiment on leached heavy loam chernozem in the Republic of Mordovia. The objects of the study are two crop rotations (grain-grass-fallow and grain-grass crop rotations) where alfalfa of the VEGA 87 variety was used as a bean component, smooth brome (Bromus inermis) Penza 1 was used as a grain component. It has been established that mineral fertilizers in grain-grass-fallow crop rotations with legumes increased productivity by 0.34-0.55, with cereals – by 0.31-0.73 tons of feed units/ha. That provided to get additional income from 1.19 to 1.40 and 1.09 to 1.47 rub/rub, respectively. Recommended doses of mineral fertilizers against soil liming by 0.5 hydrolytic acidity (h.a,) were N22-39P42K52, for grain-grass-fallow crop rotation with alfalfa and N27-71P42K52. with smooth brome. In the grain-grass crop rotation with legume and cereal components the payback of 1 kg active ingredient (a.i.) of complete mineral fertilizer was 6.13 and 6.17 kg feed units, additional income was 2.00 and 1.99 rub/rub, the productivity increased by 0.86-1.08 and 0.84-1.22 tons of feed units/ha, respectively. The payback of 1 kg of a. i. nitrogen as part of a complete mineral fertilizer in this crop rotation averaged 13.04 kg feed units versus 11.5 kg in legumes. Recommended doses of mineral fertilizers were N26-87P46K65 against the background of liming of the soil by 0.5-1.0 h. a. In crop rotation with smooth brome phosphorus-potash fertilizers should not be applied due to the low additional income (0.97-1.07 rub/rub).